Oocyte aging is controlled by mitogen‐activated protein kinase signaling. Issue 6 (1st June 2021) - Achache, Hanna; Falk, Roni; Lerner, Noam; Beatus, Tsevi; Tzur, Yonatan B.
Abstract: Oogenesis is one of the first processes to fail during aging. In women, most oocytes cannot successfully complete meiotic divisions already during the fourth decade of life. Studies of the nematode Caenorhabditis elegans have uncovered conserved genetic pathways that control lifespan, but our knowledge regarding reproductive aging in worms and humans is limited. Specifically, little is known about germline internal signals that dictate the oogonial biological clock. Here, we report a thorough characterization of the changes in the worm germline during aging. We found that shortly after ovulation halts, germline proliferation declines, while apoptosis continues, leading to a gradual reduction in germ cell numbers. In late aging stages, we observed that meiotic progression is disturbed and crossover designation and DNA double‐strand break repair decrease. In addition, we detected a decline in the quality of mature oocytes during aging, as reflected by decreasing size and elongation of interhomolog distance, a phenotype also observed in human oocytes. Many of these altered processes were previously attributed to MAPK signaling variations in young worms. In support of this, we observed changes in activation dynamics of MPK‐1 during aging. We therefore tested the hypothesis that MAPK controls oocyte quality in aged worms using both genetic and pharmacological tools. We found that in mutants with high levels of activated MPK‐1, oocyte quality deteriorates more rapidly than in wild‐type worms, whereas reduction of MPK‐1 levels enhances quality. Thus, our data suggest that MAPK signaling controls germline aging and could be used to attenuate the rate of oogenesis quality decline. Abstract : In C. elegans germline, aging leads to several changes, including crossover designation, apoptosis, and the quality of the mature oocytes. All of these were previously shown to be controlled by MAPK signaling. We show that arrested oocyte's quality is lower when MAPK is overactivated, yet it can be improved by lowering MAPK via genetic or pharmacological tools.